Análisis jurídico y doctrinario del incremento de la criminalidad, desde la perspectiva del movimiento migratorio de los países de Colombia y Venezuela al Ecuador - Benitez Curipoma, Cristian Danilo (2024)
The following Curricular Integration Work is titled: “Legal and doctrinal analysis of the increase in crime, from the perspective of the migratory movement from the countries of Colombia and Venezuela to Ecuador”, I consider it appropriate to carry out this research since although we can consider that lately In our Ecuadorian territory in recent years a large number of foreigners from the countries of Colombia and Venezuela have entered, many of them have entered formally, with all the requirements and respecting the established migration laws, likewise several of the migrants who The rate of entry into Ecuadorian territory is unknown, they enter through several irregular areas of our country, in total disregard of immigration laws. Although we can consider many of the migrants enter our territory out of necessity, in search of opportunities, many of them do not enter with the same intentions, many of them seek to commit crimes and commit actions against the security of Ecuadorians. Although it isimportant to consider that we should not generalize and criminalize all foreigners who are in our territory and we should not point out that they commit criminal actions, many of them have been the cause of various crimes committed in our country, it is evident that our legislation opens the doors to any foreign citizen to our country, even through unauthorized places, our legislation does not opt for the non-admission or deportation of foreigners. Without the respective control of the entry of foreign citizensthrough border areas and unauthorized places, informal migration becomes a problem for the increase in crime and criminality in Ecuador. The current Curricular Integration Work was carried out with the respective use and application of corresponding materials and methods in order to demonstrate the fulfillment of the objectives that we have set, that iswhy the application technique of “Surveys” and “Interviews” was used. ” which have been addressed to legal professionals, migrants and people interested in the matter, the results of which facilitated us to propose the proposal of propositional guidelines, with the purpose of guaranteeing the sovereignty and citizen security that is being violated by the presence of the phenomenon of informal migration.